2011
DOI: 10.1007/s10875-011-9623-6
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Clinical and Genetic Spectrum of Human CD40L Deficiency: The Occurrence of Paracoccidioidomycosis and Other Unusual Infections in Brazilian Patients

Abstract: CD40 ligand (CD40L) deficiency or X-linked hyper-IgM syndrome (X-HIGM) is a well-described primary immunodeficiency in which Pneumocystis jiroveci pneumonia is a common clinical feature. We have identified an unusual high incidence of fungal infections and other not yet described infections in a cohort of 11 X-HIGM patients from nine unrelated Brazilian families. Among these, we describe the first case of paracoccidioidomycosis (PCM) in X-HIGM. The molecular genetic analysis of CD40L was performed by gene sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 54 publications
0
31
0
2
Order By: Relevance
“…Opportunistic infections, especially Cryptosporidium parvum and Pneumocystis jirovecii infections, are common and prominent clinical feature of XHIGM patients [16, 17, 23]. Besides, infections caused by tubercle bacillus were detected [16, 17, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic infections, especially Cryptosporidium parvum and Pneumocystis jirovecii infections, are common and prominent clinical feature of XHIGM patients [16, 17, 23]. Besides, infections caused by tubercle bacillus were detected [16, 17, 19].…”
Section: Discussionmentioning
confidence: 99%
“…All of them responded well to antifungal therapy, and only two patients had recurrent histoplasmosis (86, 111). One case of PCM was reported in Brazil (116). It was shown that mature DCs from patients with CD40L deficiency exhibited markedly reduced IL-12 and increased IL-10 production in response to P. brasiliensis and C. albicans compared with normal controls, and T cells had significantly reduced IFN-γ production when cocultured with their DCs, whereas IL-4 and IL-5 production was increased.…”
Section: Pids Underlying Fungal Infectionsmentioning
confidence: 99%
“…Paracoccidioidomycosis can be associated with comorbidities, such as Hodgkin disease, 5 leukaemia, lymphoma 52 and carcinomas, especially lung, oropharynx and larynx carcinomas 5,52 . The use of immunosuppressive drugs, including TNF‐α blockers, 56 as well as the occurrence of X‐linked hyper‐IgM syndrome (X‐HIGM), has been reported in association with paracoccidioidomycosis 57 . Still, regarding the role played by immunosuppressive drugs, it is notable that adrenal glands are highly susceptible to P. brasiliensis infection because of the local immunosuppression caused by their high steroid concentrations 58 .…”
Section: Immunologymentioning
confidence: 99%